Acetaminophen and caffeine removal by MnOx(s) and GAC media in column experiments. Issue 1 (18th November 2020) - Miera, Rachael; Shaikh, Nabil; Artyushkova, Kateryna; Ali, Abdul-Mehdi S.; Santoro, Carlo; Thomson, Bruce M.; Howe, Kerry J.; Cerrato, José M.
Abstract : The objective of this study was to investigate the application of manganese oxide [MnO x (s) ] and granular activated carbon (GAC) media for the removal of caffeine and acetaminophen from water. Abstract : The objective of this study was to investigate the application of manganese oxide [MnO x (s) ] and granular activated carbon (GAC) media for the removal of caffeine and acetaminophen from water. Organic contaminants of emerging concern represent a developing issue due to their effects on human health and the environment. Manganese oxides are effective for water treatment because of their ability to mediate adsorption and oxidation–reduction reactions for many organic and inorganic constituents. Laboratory scale column experiments were performed using different combinations of commercial MnO x (s) and GAC for assessing the removal of caffeine and acetaminophen, and the subsequent release of soluble Mn due to the reductive dissolution of MnO x (s) . The removal of acetaminophen was detected for all media combinations investigated. However, the removal of caffeine by adsorption only occurred in columns containing GAC media. There was no removal of caffeine in columns containing only MnO x (s) media. Manganese release occurred in columns containing MnO x (s) media, but concentrations were below the secondary drinking water standard of 50 μg L −1 set by the US Environmental Protection Agency. Soluble Mn released from a first process by MnO x (s) media column was removed through adsorption into the GAC media used in a second process. The results of this investigation are relevant for implementation of MnO x (s) and GAC media combinations as an effective treatment process to remove organic contaminants from water.